KEMAMPUAN KOMUNIKASI MATEMATIS DITINJAU DARI SELF-EFFICACY SISWA PADA MATERI PROGRAM LINEAR DI SMA - Maria Nina Anggraeni; Zubaidah R; Hamdani Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research was aimed at determining how students' mathematical communication skills in solving material of “Linear Program” who have high self-efficacy, moderate self-efficacy and low self-efficacy in SMA Negeri 9 Pontianak. The method in this research is descriptive study with descriptive qualitative research form. Techniques of data collection used are measurement techniques and direct communication technique. Data collection tools used in this study were questionnaires, written tests and interviews. It was found that students with high self-efficacy were able to express daily events into language or mathematical symbols; they were able to reflect pictures into mathematical ideas and were able to explain the results of answers in their own language or words. Students with moderate self-efficacy are being able to express daily events into language or mathematical symbols, are able to reflect images into mathematical ideas and write answers given with words but are incomplete and incorrect with information contained in the problems. Students with low self-efficacy find it difficult to understand the commands of the problems and are unable to solve the problems given. Keywords: Linear Program, Mathematical Communication Skills, Self-efficacy